The association of age with acute toxicities in NRG oncology combined modality lower GI cancer trials. Issue 3 (April 2022) - VanderWalde, Noam; Moughan, Jennifer; Lichtman, Stuart M.; Jagsi, Reshma; Ballo, Matthew; VanderWalde, Ari; Mohiuddin, Mohammed; Meropol, Neal J.; Kachnic, Lisa; Berger, Adam; Ajani, Jaffer; Anne, Rani; et al.
Abstract: Purpose: Expected toxicity from chemoradiation (CRT) is an important factor in treatment decisions but is poorly understood in older adults with lower gastrointestinal (GI) malignancies. Our objective was to compare acute adverse events (AAEs) of older and younger adults with lower GI malignancies treated on NRG studies. Methods: Data from 6 NRG trials, testing combined modality therapy in patients with anal or rectal cancer, were used to test the hypothesis that older age was associated with increased AAEs. AAEs and compliance with protocol-directed therapy were compared between patients aged ≥70 and < 70. Categorical variables were compared across age groups using the chi-square test. The association of age on AAEs was evaluated using a covariate-adjusted logistic regression model, with odds ratio (OR) reported. To adjust for multiple comparisons, a p -value <0.01 was considered statistically significant. Results: There were 2525 patients, including 380 patients ≥70 years old (15%) evaluable. Older patients were more likely to have worse baseline performance status (PS 1 or 2) (23% vs. 16%, p  = 0.001), but otherwise baseline characteristics were similar. Older patients were less likely to complete their chemotherapy (78% vs. 87%, p  < 0.001), but had similar RT duration. On univariate analysis, older patients were more likely to experience grade ≥ 3 GI AAEs (36% vs. 23%, p  < 0.001), and less likely to experience grade ≥ 3 skin AAEs (8% vs. 14%, p = 0.002). On multivariable analysis, older age was associated with grade ≥ 3 GI AAE (OR 1.93, 95% CI: 1.52, 2.47, p < 0.001) after adjusting for sex, race, PS, and disease site. Conclusions: Older patients with lower GI cancers who underwent CRT were less likely to complete chemotherapy and had higher rates of grade 3+ GI AAEs. These results can be used to counsel older adults prior to treatment and manage expected toxicities throughout pelvic CRT.